Implementation Opportunities of Green Accounting for Activity-Based Costing (ABC) in Romania - Sorinel Capusneanu (Theoretical and Applied Economics, 2008)
This article refers to implementation opportunities of green accounting for the Activity- Based Costing method. It shows why we choose Activity-Based Costing method and what must be done in this way. Green accounting observes the specific principles of the Activity-Based Costing method. It also represents the advantages and disadvantages of the green accounting into an enterprise in case of Activity-Based Costing implementation. The paper describes the stages we must follow in case of implementation of green accounting alongside Activity-Based Costing method into an enterprise.